Accounting information systems and their impact on human resources engineering (an analytical study of the opinions of a sample of workers in University institution ) - Mohsin abbood Bandar; Abeer M. Mahdi AL-shammari; Muntadher kadhim shamran (Peerian Journals Publishing, 2023)
Accounting information systems are among the oldest information systems in institutions, because these systems are of great importance in identifying the economic and financial reality of the institution, and identifying the relationship of the institution with its surrounding environment. The study aims to identify the impact of accounting information systems in the university institution on human engineering. The descriptive analytical method was used by collecting data through a distributed questionnaire. After the statistical analysis of the questionnaire, the statistical results showed that there are correlations and influences between the research variables
Keywords: accounting information systems; human engineering